FAKTOR PENDORONG REMAJA DIBAWAH UMUR MENGGUNAKAN VAPE DI SATUTUJU KOPI PEKANBARU - Febriana Azahrha; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The phenomenon of vaping is no longer unfamiliar to Indonesian society. This trend has sparked curiosity among various groups of people as it is seen as unique and different. Some individuals consider vaping as an alternative to quit smoking. Similarly, underage adolescents, who are prohibited from using vape, are also drawn to this trend. This phenomenon is particularly prevalent among school students who enjoy hanging out at coffee shops. This research was conducted at Satutuju Kopi Pekanbaru with the aim of understanding the driving factors behind underage adolescents using vape and the health effects of vape use on students. The research employed a descriptive qualitative research method, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The study involved six primary informants and two supporting informants as research subjects. The results reveal that the driving factors behind underage adolescents using vape and the effects of vape use on students are influenced by environmental factors and lifestyle choices. The perceived impacts include addiction, leading to dependency and difficulty in quitting. This research provides valuable insights into the driving factors behind underage adolescents using vape at Satutuju Kopi Pekanbaru and its impact on their health. The implications of this research can be used to develop effective prevention and intervention strategies to reduce underage vape use and increase awareness of the health risks associated with vaping. Keyword: Vape, Teenager, Rational Choice.